Pengaruh Pendidikan Kesahatan tentang Nutrisi Gizi Seimbang saat Menstruasi untuk Mencegah Anemia terhadap Pengetahuan Remaja Putri - Deni Riliti (Jurnal Medika Hutama, 2022)
Anemia is a decrease in Hemoglobin (Hb) levels, an inadequate elements or lack of nutrients needed for the formation of red blood celss which results in decreased blood oxygen carried capacity. Anemia was caused by blood lost, inadequate consumption of food. This study was aimed to determine the influence of health education about balanced nutrition in menstruation to prevent anemia against. The design of this research study was “Quasy Experiment” using the draft “With One Group Design” which is divided into an experimental group pre test and post test. The study was conducted to adolescence on Kayu Ara Permai village. Total sample was 34 adolescence who fit the inclusion criteria and the using simple purposive sampling technique. Measuring intrument is using questionnaire. The analysis used univariate and bivariate analysis using dependent sampel T test. The result was showed a influence of health education about balanced nutrition in menstruation to prevent anemia to an experimental group pre test and post test after given intervention with p value (0,000) < (0,05). This means that health education about balanced nutrition effective to prevent anemia when in menstruation, so it was suggested to adolescence used the way to prevent anemia and increased knowledge about balanced nutrition when in menstruation to prevent anemia.